Finite element modeling of rivet fastened rectangular hollow flange channel beams subject to local buckling - Siahaan, Ropalin; Keerthan, Poologanathan; Mahendran, Mahen (Engineering structures, 2016)
•Investigated section moment capacities of rivet fastened rectangular hollow flange channel beams.•Suitable finite element models were developed and validated using test results.•Investigated the effect of rivet fastening on the flexural behavior and capacities.•Current design rules in AS/NZS 4600 were found to be inadequate.•Developed Direct Strength Method based equations to determine the section moment capacities. The innovative, rivet fastened Rectangular Hollow Flange Channel Beam (RHFCB) is a new type of cold-formed steel section, proposed as an extension to the widely researched hollow flange beams. The hollow flange beams have garnered much interest in the past due to the sections having capacities more typically associated with hot-rolled steel sections. This paper presents the details of finite element models developed to simulate fifteen back to back, four-point bending tests, previously carried out by the authors to investigate the section moment capacities of rivet fastened RHFCBs. The test specimens were laterally restrained to ensure predominant local buckling failures, commonly observed in short-span hollow flange beams. The developed finite element models were able to simulate the test results in terms of ultimate moment capacities, applied moment versus deflection graphs and deformation modes. In addition, elastic buckling analysis results based on the finite element models also agreed well with the results from Thin-Wall finite strip analyses. Upon validation, finite element modeling was extended to include a larger slenderness region in a parametric study. The ultimate moment capacities from the tests and finite element analyses were compared with currently available design standards: AS/NZS 4600, AS 4100 and AISI S100. The suitability of the Direct Strength Method was also investigated for the rivet fastened RHFCBs and a suitable modification was proposed.